Biomedizinische Technik - Medizinische Informatik - Dickhaus, Hartmut (Biomedizinische Technik, 2015)
The sixth volume in the biomedical engineering textbook series addresses the interdisciplinary field of health informatics. The book discusses its pragmatic applications in clinical information systems as well as medical bioinformatics in research.